MUATAN NILAI DAN PRINSIP PIAGAM MADINAH DAN PANCASILA: ANALISA PERBANDINGAN - Fahruddin, M. Mukhlis (ULUL ALBAB Jurnal Studi Islam, 2011)
Madinah charter consist of humane ideas of civil society which are relevant to development and needs of world society and has become a modern way of life. Agreeing with Madinah charter Ideas, the founding fathers of Indonesia adopt it into Jakarta charter which is later called as Pancasila. The content of Madinah charter and Pancasila have smililarities as a SAWaâ€™ or a exalted agreement of humane society. Pancasila is a dignifiying submission of all the national element to establish, love and maintain Indonesia. Similarly, Madinah Charter is noble agreement to defend Madinah as a nation. Both of these charters include basic principles such as: wisdom, brotherhood, equality, tolerance, democracy, cooperation, and justice.Â